UTILITY OF matK GENE AS DNA BARCODE TO ASSESS EVOLUTIONARY RELATIONSHIP OF IMPORTANT TROPICAL FOREST TREE GENUS Mangifera (Anacardiaceae) IN INDONESIA AND THAILAND - Topik - Hidayat; Adi - Pancoro; Diah - Kusumawaty (SEAMEO BIOTROP, 2011)
MaturaseK (matK) gene of chloroplast DNA has been served as appropriate candidate to be a DNA barcode in angiosperms. Using this DNA marker, 19 species of genus Mangifera, one of ecologically important crop, collected from Indonesia and Thailand were analyzed. Phylogenetic analysis using parsimony method revealed that the gene could clasify Mangifera into three major groups, namely group I, II, and III. Moreover, the matK barcode can identify Mangifera species that is originated from Thailand. Although this classification system is different with the previous system, it can provide a new information about Mangifera taxonomy. Results further exhibited that DNA sequences of the matK of two Mangifera species (M. laurina dan M. macrocarpa) are different between Indonesia and Thailand specimens.Â Keywordsâ€” DNA barcode, Mangifera, matK gene, parsimony, phylogenetic analysis